High‐Speed Antagonistic Shape Memory Actuator for High Ambient Temperatures. Issue 9 (3rd May 2022) - Britz, Rouven; Rizzello, Gianluca; Motzki, Paul
Abstract : This work presents the development of an innovative shape memory alloy (SMA) actuator principle, which allows high‐speed switching cycles through the decoupling of antagonistically arranged SMA wires. Being optimized for the use at high ambient temperatures up to 65 °C, a possible application area is the active venting of injection molds where it can be used to expel air, which is trapped during the injection mold process. The patented actuator principle is based on a decoupled agonist–antagonist SMA‐spring system and allows a high‐speed closing movement by a compact and lightweight design. Another innovation compared to conventional antagonistic SMA actuator systems is the integrated fail‐safe mechanism, which guarantees a defined closed state in case of power failure. Subsequently, in the motivation the need for active venting valves for injection molding is first described. Second, the novel actuator principle is introduced, and the development of an electronics concept is discussed. Finally, the design process, assembly, and validation of two iterations of the actuator prototype are presented. The final prototype validation measurements showcase high performance by valve strokes of 1 mm within 100 ms at ambient temperature of 65 °C. Abstract : Herein, a novel shape memory alloy (SMA) wire actuator principle for fast switching at high ambient temperatures is presented. A complete prototype including power electronics is validated in a valve application. The prototype validation measurements showcase high performance by valve strokes of 1 mm within 100 ms at ambient temperature of 65 °C.